Development of a fed-batch process for a recombinant Pichia pastoris Δoch1 strain expressing a plant peroxidase. Issue 1 (December 2015) - Gmeiner, Christoph; Saadati, Amirhossein; Maresch, Daniel; Krasteva, Stanimira; Frank, Manuela; Altmann, Friedrich; Herwig, Christoph; Spadiut, Oliver
Abstract Pichia pastoris is a prominent host for recombinant protein production, amongst other things due to its capability of glycosylation. However, N-linked glycans on recombinant proteins get hypermannosylated, causing problems in subsequent unit operations and medical applications. Hypermannosylation is triggered by an α-1, 6-mannosyltransferase called OCH1. In a recent study, we knocked out OCH1 in a recombinantP. pastoris CBS7435 MutS strain (Δoch1 ) expressing the biopharmaceutically relevant enzyme horseradish peroxidase. We characterized the strain in the controlled environment of a bioreactor in dynamic batch cultivations and identified the strain to be physiologically impaired. We faced cell cluster formation, cell lysis and uncontrollable foam formation. In the present study, we investigated the effects of the 3 process parameters temperature, pH and dissolved oxygen concentration on 1) cell physiology, 2) cell morphology, 3) cell lysis, 4) productivity and 5) product purity of the recombinant Δoch1 strain in a multivariate manner. Cultivation at 30°C resulted in low specific methanol uptake during adaptation and the risk of methanol accumulation during cultivation. Cell cluster formation was a function of the C-source rather than process parameters and went along with cell lysis. In terms of productivity and product purity a temperature of 20°C was highly beneficial. In summary, we determined cultivation conditions for a recombinantP. pastoris Δoch1 strain allowing high productivity and product purity.